(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the prevalence of malnutrition and related factors among elderly patients at Gia Dinh People’s hospital, Ho Chi Minh City in 2023 Methods: A cross-sectional study was conducted on 97 elderly inpatients at the Department of Geriatrics, Gia Dinh People’s Hospital, Ho Chi Minh City, from February to May 2023. The collected information includes nutritional status (MNA-SF, BMI), characteristics of sociology and pathology, laboratory findings. Results: The malnutrition rate in elderly patients identified with MNA-SF was 75.3% and 25.7% with BMI. The study suggests that there exist statistically significant relationships between malnutrition rate (according to MNA-SF) and age distribution, income source, dyslipidemia, and hemoglobin (p < 0.05). Conclusions: The percentage of elderly patients with malnutrition is rather high. Therefore, it is necessary to have individualized nutritional intervention solutions for each elderly inpatient before, during, and after hospitalization.